Reading Aboriginal women's autobiography - Brewster, Anne. (Melbourne : Sydney University Press in association with Oxford University Press, 1996)
Discussion and analysis of women's life histories through examination of work of Sally Morgan, Ruby Langford and Alice Nannup and themes of Aboriginality, race and gender and family and storytelling respectively; introductory chapter discusses the styles and themes of women's autobiography; includes a list of published autobiographies for further reading; suitable for secondary students.
Bibliography: p. 57-64.
Keywords: Autobiography -- Women authors; Women, Aboriginal Australian -- Biography -- History and criticism; Aboriginal Australians -- Social conditions; Australian literature -- 20th century -- History and criticism; Australian literature -- Women authors -- History and criticism; Australian literature -- Aboriginal authors -- History and criticism; History - Biographies - Indigenous - Autobiographies; Social identity - Aboriginality; Race relations - Racism - Stereotyping; Literature and stories - Authors; Literature and stories - Story telling and story tellers; Family; Australia